Twelve-Week Yoga vs. Aerobic Cycling Initiation in Sedentary Healthy Subjects: A Behavioral and Multiparametric Interventional PET/MR Study - van Aalst, June; Jennen, Lise; Demyttenaere, Koen; Sunaert, Stefan; Koole, Michel; Ceccarini, Jenny; Van Laere, Koen (Frontiers in Psychiatry, 2021)
Interventional yoga studies with an active control group remain scarce and are important to clarify the underlying neurobiology. We conducted an interventional study in healthy controls using simultaneous positron emission tomography/magnetic resonance (PET/MR) imaging and psychometric scales. Thirty healthy, female volunteers (28.4±8.4 yrs) participated and were randomly assigned to a 12-week yoga or indoor cycling intervention. Before and after the intervention, [18F]FDG and [11C]UCB-J PET was performed on a simultaneous GE Signa PET/MR with volumetric imaging. Psychometric scales were evaluated on affect, mindfulness, stress, worrying, self-compassion and interoceptive awareness. Yoga subjects scored higher on interoceptive awareness compared to baseline (p<0.001). Cognitive (P=0.009) and overall cognitive functioning (P=0.01) improved after the yoga intervention compared to the cycling group. We did not observe significant differences in glucose metabolism, synaptic density or grey matter concentration. The indoor cycling group did not show changes in psychometric variables, but significant increases in relative glucose metabolism were observed in the parahippocampal/fusiform gyrus and cerebellum (P<0.001). In conclusion, twelve weeks of yoga practice has significant effects on interoceptive awareness and perceived cognitive function in starters. Longer interventions and/or higher frequency of yoga practice may be needed to detect cerebral metabolic and/or morphologic effects on the macroscopic level.